Desempenho na tomada de decisão baseada em mindset, emoções básicas, velocidade heurística e aversão ao risco no ambiente do Iowa Gambling Task - Rafael Nunes da Silva (2024)
Studies on Mindset have been highlighted in the literature as a significant factor in human decision-making. Mindset, along with emotions, influences the decision-making process and is a crucial aspect in the research agenda, impacting organizational performance. The aim of this study is to evaluate the performance and basic emotions of individuals with different Mindsets when exposed to emotional video content, both negative and positive, before executing the Iowa Gambling Task (IGT) and to investigate possible differences in performance and basic emotions among them during decision-making. The experiment involved 93 individuals, both women and men, aged between 25 and 65 years, who are active in the job market. Questionnaires, videos, validated tests, and facial expression readers were used. Participants filled out a Socioeconomic Questionnaire to collect basic data. Subsequently, they completed the PANAS scale (Positive Affect and Negative Affect Scale). Then, a Mindset questionnaire was applied to classify each participant. Subsequently, part of the group with "Growth Mindset or Above Average" was stimulated with positive emotion videos, while the other part, with "Growth Mindset or Below Average," was exposed to negative emotion videos. After watching the videos, participants started the Iowa Gambling Task (IGT), where their faces were filmed for later analysis using the FaceReader Software. The results highlight the influence of Mindset on participants' responses, including risk aversion, performance, emotions, and heuristic speed. While significant differences were found in some measures between the above-average and below-average Mindset groups, others did not show differences. In conclusion, this study emphasizes the importance of interactions between Mindset, emotions, and performance in decision-making, highlighting the complexity of these relationships. The adherence of the model to the empirical data validates the proposed theoretical structure, providing a solid foundation for future research and practical interventions.